Hubungan Ekspresi Sex Determining Region Y Box 2 (SOX2) dengan Grading Histopatologi, Invasi Vaskular Intramural dan Ekstramural pada Adenokarsinoma Kolorektal - Rizki, Diana; Delyuzar, Delyuzar; Alferraly, T. Ibnu; Betty, Betty; Soekimin, Soekimin; S. Lukito, Joko (Majalah Patologi Indonesia, 2023)
Background Incidence and mortality of colorectal carcinoma (CRC) worldwide varies widely (10 times). Ninety percent colorectal malignancies are adenocarcinomas. Expression SOX2 is associated with high tumor grade, invasion, metastasis as well as a prognostic predictor of colorectal adenocarcinoma. Objective: Analyze the association of SOX2 immunohistochemistry expression with histopathological grading, intramural and extramural vascular invasion in colorectal adenocarcinoma. Methods Analytical study using a cross-sectional approach on 35 samples from the Anatomic Pathology Unit, H. Adam Malik Hospital, Medan. Immunohistochemical staining of SOX2 mouse monoclonal antibody (Bioassay Technology Laboratory) was performed and expression assessed as low (0-3) and high (4-6). Differences in expression were analyzed by Chi-square and Mann-Whitney correlation tests. Results The most patients with colorectal adenocarcinoma were at age of 51-60 years (34.3%), male sex was more common (60%), the most tumor location was in the rectum (40%), the most depth of invasion was T3 (74.3%) , low grade was more common (60%), more intramural vascular invasion was found (40%), and the highest expression of SOX2 was found to high expression which mostly in the nucleus and cytoplasm (84.6%) There was no significant association between SOX2 expression and histopathological grading (p= 0.884) and there was no significant association between SOX2 expression and vascular invasion, both intramural and extramural (p= 0.390). Conclusion There was no significant association between SOX2 expression and histopathological grading and vascular invasion, both intramural and extramural.